2017
DOI: 10.1149/2.0301706jss
|View full text |Cite
|
Sign up to set email alerts
|

The Gadonanotubes as High-Performance MRI Contrast Agents: The Unappreciated Role of the Carbon Nanotube Component at Low Magnetic Fields

Abstract: The Gadonanotubes (GNTs) are the highest-performing T 1 -weighted MRI contrast agent material known with a relaxivity of ∼160 mM −1 s −1 per Gd 3+ ion at 1.5 T. In this work, the contribution of carbon-based free radicals at defect sites on the sidewalls of the ultra-short carbon nanotube (US-tube) component of the GNTs to the T 1 relaxation time has been investigated by Nuclear Magnetic Resonance Dispersion (NMRD) and Electron Paramagnetic Resonance (EPR) studies. The NMRD results indicate that carbon-based r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 58 publications
(86 reference statements)
2
15
0
Order By: Relevance
“…(B) T1‐weighted magnetic resonance imaging (MRI) phantoms of Gd 3+ n@US‐tubes and Magnevist™ at the same concentration; pure water is also shown. Reprinted with permission from, copyright 2017, the Electrochemical Society. (C) MR images of nanodiamond samples.…”
Section: Potential Advantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…(B) T1‐weighted magnetic resonance imaging (MRI) phantoms of Gd 3+ n@US‐tubes and Magnevist™ at the same concentration; pure water is also shown. Reprinted with permission from, copyright 2017, the Electrochemical Society. (C) MR images of nanodiamond samples.…”
Section: Potential Advantagesmentioning
confidence: 99%
“…Tóth et al found the TR of Gd@C 60 [C(COOH) 2 ] 10 decrease when it is disaggregated, from TR = 2.6 ns to TR = 1.2 ns. In the case of gadonanotubes, NMRD studies have shown, gadonanotubes have relaxation profiles characteristic of gadolinium ions co‐ordinated to a slowly tumbling environment …”
Section: Potential Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, transition metals (typically Fe, Co, or Ni) usually used as catalyst in CVD method in the production of carbon nanotubes can remain after the synthesis of CNTs as paramagnetic impurities being active in an acceleration of nuclear relaxation processes. The presence of paramagnetic enhancement of R 1 coming from the catalyst in pristine CNTs has been reported proving their efficiency. , To describe NMRD data in studied supernatants, it is important to discuss the potential sources of spin–lattice relaxation times shortening in the systems of this type, which can result from both the influence of spatial constraints imposed by carbon nanotubes on water molecules in the MWCNTs suspensions and the presence of paramagnetic impurities of carbon nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that in MWCNTs suspensions, water can also be entrapped between the not perfectly separated ropes of carbon nanotubes which can enhance the spin–lattice relaxation. The presence of a small fraction of that kind of water can significantly affect the shape of the profile in the low magnetic fields. , In the protein solutions it has been shown that the existence of trapped water molecules can lead to strong R 1 dispersion profiles stretched toward low frequencies . The enormous frequency dependence of T 1 has been reported for polar liquids displaying strong adsorption onto the internal surface of porous systems without paramagnetic impurities.…”
Section: Resultsmentioning
confidence: 99%